REKONTRUKSI KURIKULUM MERDEKA BELAJAR DI SMK DARUNNAJAH BANJARMANGU KABUPATEN BANJARNEGARA PROVINSI JAWA TENGAH - Feri Tulistiyono; Rifqi Muntaqo (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2022)
The reconstruction of the independent curriculum is an effort to optimize the quality of education in Indonesia based on the interests and talents of learners. The